Long-Term Impact of an Educational Antimicrobial Stewardship Program on Management of Patients with Hematological Diseases - Ana Belén Guisado-Gil; Manuela Aguilar-Guisado; Germán Peñalva; José Antonio Lepe; Ildefonso Espigado; Eduardo Rodríguez-Arbolí; José González-Campos; Nancy Rodríguez-Torres; María Isabel Montero-Cuadrado; José Francisco Falantes-González; Juan Luis Reguera-Ortega; María Victoria Gil-Navarro; et al. (MDPI AG, 2021)
Antimicrobial stewardship programs (ASPs) in hematological patients are especially relevant. However, information about ASPs in this population is scarce. For 11 years, we quarterly assessed antimicrobial consumption and incidence and death rates of multidrug-resistant (MDR) bloodstream infections (BSI) in the hematology Department. Healthcare activity indicators were also monitored yearly. We performed an interrupted time-series analysis. Antimicrobials showed a sustained reduction with a relative effect of −62.3% (95% CI −84.5 to −40.1) nine years after the inception of the ASP, being especially relevant for antifungals (relative effect −80.4%, −90.9 to −69.9), quinolones (relative effect −85.0%, −102.0 to −68.1), and carbapenems (relative effect −68.8%, −126.0 to −10.6). Incidence density of MDR BSI remained low and stable (mean 1.10 vs. 0.82 episodes per 1000 occupied bed days for the pre-intervention and the ASP period, respectively) with a quarterly percentage of change of −0.3% (95% CI −2.0 to 1.4). Early and late mortality of MDR BSI presented a steady trend (quarterly percentage of change −0.7%, 95% CI −1.7 to 0.3 and −0.6%, 95% CI −1.5 to 0.3, respectively). Volume and complexity of healthcare activity increased over the years. The ASP effectively achieved long-term reductions in antimicrobial consumption and improvements in the prescription profile, without increasing the mortality of MDR BSI.